A critical analysis of securities crime in Canada - Russel, Bronwen (Canadian journal of criminology and criminal justice, 2019)
Canada's securities markets serve an important function by (a) enabling corporations to buy, sell, trade, or otherwise use securities to generate or maintain capital, and (b) encouraging investors to participate. Protecting these markets from crime is difficult. A dialectical analysis of the decisions, extending orders, orders, settlement agreements, and official news releases from the provincial securities regulators between the years 1986 and 2012 revealed how the opportunities for and the ability to conceal such crimes are created. Institutions, power, and ideology are the underlying concepts used to explain the criminogenic nature of the markets